Cognitive Approach to the Stereotypical Placement of Women in Visual Advertising Space - Amankevičiūtė, Simona (Respectus Philologicus, 2013)
This article conceptualizes the image of women in the sexist advertisements of the 1950s and 60s and in current advertising discourse by combining the research traditions of both cognitive linguistics and semiotic image analysis. The aim of the research is to try to evaluate how canonical positionings of women in the hyperreality of advertisements may slip into everyday discourse (stereotype space) and to present an interpretation of the creators’ visual lexicon. It is presumed that the traditional (formed by feminist linguists) approach to sexist advertising as an expression of an androcentric worldview in culture may be considered too subjectively critical. This study complements an interpretation of women’s social roles in advertising with cognitive linguistic insights on the subject’s (woman’s) visualisation and positioning in ad space. The article briefly overviews the feminist approach to women’s place in public discourse, and discusses the relevance of Goffman’s Gender Studies to an investigation of women’s images in advertising. The scholar’s contribution to adapting cognitive frame theory for an investigation of visuals in advertising is also discussed. The analysed ads were divided into three groups by Goffman’s classification, according to the concrete visuals used to represent women’s bodies or parts thereof: dismemberment, commodification, and subordination ritual. The classified stereotypical images of women’s bodies are discussed as visual metonymy, visual metaphor, and image schemas.